Unveiling Online Collaborative Learning and Sense of Community in an English Drama Course: Indonesian EFL Undergraduate Students View - Supeno; Febriyanti, Rina Husnaini (ELE Reviews: English Language Education Reviews, 2024)
A sense of community enhances the exchange of information, fosters cooperation and support, and strengthens commitment to group objectives. Numerous studies have investigated the importance of community and collaborative learning activities within online environments. However, online collaborative learning and a sense of community in an English Drama Course (EDC) are still under-explored. The current study aims to fill that gap by following a group of 131 undergraduate students participating in a 16-week online EDC. Data was gathered via a questionnaire and a semi-structured interview coded by following the dimensions of the questionnaire. The current study reveals that students view online collaborative learning in an EDC positively and generate interactive engagement, teamwork, creativity, efficacy, social skills, problem-solving skills, idea generation, and enjoyment, which is particularly advantageous for navigating unfamiliar subject matter or foreign language contexts. The collaborative learning process hinges on establishing a robust sense of community, emphasizing shared objectives, effective communication, trust, collective problem-solving, and a supportive environment, highlighting the importance of addressing barriers to fostering this communal ethos for successful collaboration. The implications of this study might catalyze researchers and educators to consider developing a sense of community in online collaborative environments.